Measuring Ethanol Content in Kolesom, a Javanese Wine, and Traditional Wine of Bali by Gas Chromatography (GC): Ensuring Halal Label for Traditional Herbal Medicine - Rachmaniah, Orchidea; Budiono, Ryanto; Sumiyani, Ririn; Sabrina, Melia Indah; Sakdiyah, Sakdiyah; Sabella, Julietta Salwa; Safira, Chyntia Aulia; Safitri, Bella Intan (Halal Center ITS, 2023)
Wine is an alcoholic drink that results from the fermentation of grape juice with the help of microbes. One of the variants of wine circulating in Indonesia is wine Kolesom. Kolesom, also known as ginseng wine. Gingseng/kolesom/temulawak is classified as grapes wine with other food ingredients as an addition. It contains EtOH in between 7-24 %v/v according to the quality standard of Kolesom in The Regulation of the National Agency of Drug and Food Control of Republic Indonesia (BPOM) No. 5/2021. Kolesom extracts, considered nutritious for health, are added to grape juice, though it is Khmer and haram. In traditional herbal medicine, kolesom usually use as an addition, giving the body a strong taste, warm effect, and vitality. Adding kolesom in Jamu is a choice depending on the customer's favor. Kolesom wine is classified as B-class liquor, containing 5-20% v/v ethanol. Considering that most Indonesian citizens are Muslim, it is necessary to analyze and cross-check information to the customer about the level content of the alcohol in Javanese wine, kolesom. Ensuring the correct information to the customer and halal lifestyle. Gas chromatography equipped with a flame ionized detector (GC-FID) is proposed as a method for analyzing the ethanol (EtOH) content in kolosem, Javanese wine, as well as the traditional wine of Bali. The results showed that the proposed GC-FID method was well-validated.